Knowledge, Practices and Anxiety related to Corona Virus Disease-19 (COVID-19) among Nursing Students in Nepal - Shrestha, Sandhya; Tuladhar, Jyoti Badan; Thapa, Namrata (Journal of Lumbini Medical College, 2021)
Introduction: COVID-19 is a pandemic that emerged and rapidly spread throughout the world in no time. Nursing students are the foundation of nursing profession and they have enormous role to control the spread of the disease in society. The present study was conducted to assess knowledge, practice and anxiety related to COVID-19 among nursing students of Nepal and to find out the correlation between anxiety and knowledge and practice. Methods: A descriptive cross-sectional survey was conducted among 214 Proficiency Certificate Level and Bachelor of Sciences in Nursing students of Nursing Programme, Manipal College of Medical Sciences. Data were collected from 25th May to 2nd June 2020 through self-developed structured questionnaire to measure knowledge and practice whereas, a validated “Self -rating Anxiety scale (SAS)” was used to measure anxiety level via Google form. Data were analyzed using descriptive and inferential (spearman rho correlation) statistics. Results: Majority (73.80%) were from age group 16-20 years of age with mean age of 19.33±1.96 years. Majorities (83.60%) were Hindus. More than half (57.50%) of the respondents had adequate knowledge regarding corona virus infection, 58.90% had good practice and only 6.10% had mild to moderate anxiety level. There was no significant correlation of anxiety with knowledge (p=0.857) and practice (p=0.375). Conclusion: The study showed that more than half of the nursing students had inadequate knowledge, poor practices regarding corona virus infection and very few had mild to moderate anxiety level. Anxiety was not related to knowledge and practice regarding corona virus infection.